A Dictionary of Mupun - Frajzyngier, Zigmunt (Sprache und Oralität in Afrika. Frankfurter Studien zur Afrikanistik. Hg. von Herrmann Jungraithmayr, 1991)
Mupun is an Afro-Asiatic language spoken in Plateau State in central Nigeria, in an area within the Lankan District. It is considered a dialect of Mwaghavul.